2018
DOI: 10.1039/c8cc05560b
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional supramolecular vesicles for combined photothermal/photodynamic/hypoxia-activated chemotherapy

Abstract: Multifunctional supramolecular vesicles were constructed by self-assembly of water-soluble pillar[5]arene and near infrared-absorbing guest G. They exhibited remarkable antitumor efficacy through simultaneous combination of photothermal, photodynamic and photodynamic-triggered hypoxia-activated chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…In particular, mitochondria are susceptible to ROS, which include peroxides ($O 2 ), superoxide ($O 3 ), the hydroxyl radical ($OH), and singlet oxygen ( 1 O 2 ). 71,72 Photosensitizers are one kind of the most popular molecules for producing ROS. Fan's group prepared a supramolecular vesicle based on pillar [5]arene and an NIR-absorbing diketopyrrolopyrrole (DPP)-based guest G, and finally the hypoxiaactivated prodrug tirapazamine (TPZ) was encapsulated into the vesicle.…”
Section: Mof Nanocarriers For Stimuli-responsive Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, mitochondria are susceptible to ROS, which include peroxides ($O 2 ), superoxide ($O 3 ), the hydroxyl radical ($OH), and singlet oxygen ( 1 O 2 ). 71,72 Photosensitizers are one kind of the most popular molecules for producing ROS. Fan's group prepared a supramolecular vesicle based on pillar [5]arene and an NIR-absorbing diketopyrrolopyrrole (DPP)-based guest G, and finally the hypoxiaactivated prodrug tirapazamine (TPZ) was encapsulated into the vesicle.…”
Section: Mof Nanocarriers For Stimuli-responsive Drug Deliverymentioning
confidence: 99%
“…Fan's group prepared a supramolecular vesicle based on pillar [5]arene and an NIR-absorbing diketopyrrolopyrrole (DPP)-based guest G, and finally the hypoxiaactivated prodrug tirapazamine (TPZ) was encapsulated into the vesicle. 71 Once the system was irradiated by 660-nm laser, 1 O 2 molecules were produced to treat cancer. Rui et al designed a photodynamic therapy supramolecular vesicle.…”
Section: Mof Nanocarriers For Stimuli-responsive Drug Deliverymentioning
confidence: 99%
“…PAI can overcome the traditional optical penetration limitations (e.g., fluorescence imaging) since it detects phonons rather than photons under light excitation, providing superior spatial resolution, high contrast, and deep tissue penetration [7,[9][10][11]. To date, various optical agents have been developed for PAI/PTT theranostics, including small molecule dyes, metallic nanoparticles, and carbon nanomaterials [12][13][14][15][16]. Nevertheless, small molecule dyes usually suffer from photobleaching, while metallic nanoparticles encounter severe biotoxicity and carbon nanomaterials have broad PAI spectra without a specific wavelength and a low extinction coefficient for PAI and PTT [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Local hyperthermia can disassemble amyloid deposits by interfering with their growth . Many breakthroughs in the research and applications of photothermal agents have been reported . Nevertheless, materials currently under investigation for photothermal disintegration of matured fibrils are limited to gold and carbon‐based nanostructures.…”
Section: Introductionmentioning
confidence: 99%